The efficacy of a blended motivational interviewing and problem solving therapy intervention to reduce substance use among patients presenting for emergency services in South Africa: A randomized controlled trial - Sorsdahl, K.; Stein, D.J.; Corrigall, J.; Cuijpers, P.; Smits, N.; Naledi, T.; Myers-Franchi, Bronwyn (2015)
Background: The treatment of substance use disorders is a public health priority, particularly in South Africa where the prevalence of these disorders is high. We tested two peer-counsellor delivered brief interventions (BIs) for risky substance use among adults presenting to emergency departments (EDs) in South Africa.